Agreement between careHPV and hybrid capture 2 in detecting high‐risk HPV in women in Tanzania. (13th February 2021) - Katanga, Johnson; Kjaer, Susanne K.; Manongi, Rachel; Pembe, Andrea B.; Iftner, Thomas; Waldstrom, Marianne; Mwaiselage, Julius; Rasch, Vibeke
Abstract: Introduction: Visual inspection of the cervix with acetic acid is used to control the burden of cervical cancer in low‐ and middle‐income countries. This method has some limitations and HPV DNA testing may be an alternative, but it is expensive and requires a laboratory setup. Cheaper and faster HPV tests have been developed. This study describe the agreement between a fast HPV test ( care HPV) and hybrid capture 2 (HC2) in detection of high‐risk HPV among Tanzanian women. Material and methods: The study involved women attending routine cervical cancer screening at the Ocean Road Cancer Institute and Kilimanjaro Christian Medical Centre in Tanzania. The women were offered HIV testing. Two cervical samples were subsequently obtained; the first sample was processed at the clinics using care HPV and the second sample was transported to Denmark and Germany for cytology and HC2 analysis. Kappa statistic was calculated to assess the agreement between care HPV and HC2. The sensitivity, specificity and predictive values of care HPV were calculated using HC2 as reference. The analyses were done for the overall study population and stratified by testing site and HIV status. Results: A total of 4080 women were enrolled, with 437 being excluded due to invalid information, lack of care HPV or HC2 results. Overall agreement between the tests was substantial with a kappa value of 0.69 (95% confidence interval [CI] 0.66‐0.72). The sensitivity and specificity of care HPV was 90.7% (95% CI 89.6‐91.8) and 84.2% (95% CI 81.2–86.8), respectively. The agreement was similar in the stratified analyses where the kappa values were 0.75 (95% CI 0.70‐0.79) in women aged 25‐34, 0.66 (95% CI 0.62‐0.70) in women aged 35–60, 0.73 (95% CI 0.70‐0.77) at the Ocean Road Cancer Institute, 0.64 (95% CI 0.60‐0.69) at the Kilimanjaro Christian Medical Center, 0.73 (95% CI 0.68‐0.79) in HIV‐positive and 0.66 (95% CI 0.63‐0.70) in HIV‐negative women. The kappa value of 0.64 (95% CI 0.39‐0.88) for cervical high‐grade lesions indicates a substantial agreement between care HPV and HC2 in detecting HPV among women with cervical high‐grade lesions. Conclusions: A substantial agreement was found between care HPV and HC2 in detecting HPV overall as well as detecting HPV among women with cervical high‐grade lesions. However, given the limited resources available in low and middle‐income countries, the HPV testing assay should be weighed against the cost‐effectiveness of the test.